Recent development of nanomedicine for the treatment of bacterial biofilm infections. Issue 1 (14th October 2020) - Xiu, Weijun; Shan, Jingyang; Yang, Kaili; Xiao, Hang; Yuwen, Lihui; Wang, Lianhui
Abstract: Bacterial biofilm related infections are ever growing issues for global medical community. Traditional antibiotic therapy is usually ineffective for treating them because the bacteria inside biofilms have evolved with multiple mechanisms to evade antibiotic challenge. Hence, effective therapeutic strategy with novel antibiofilm mode of action is highly desired. In this context, nanomedicine has drawn great attentions and has been proven promising to prevent and eliminate bacterial biofilms. In this review, we focus on the recent advance of nanotechnology‐based strategies and nanoagents for combating bacterial biofilm infections. First, typical antibiofilm nanotechnologies utilized different chemical, physical, and biological properties of nanomaterials are discussed. Second, smart nanoagents that can responsive to biofilm microenvironment, including pH, H2 O2, and enzymes, are shown. Third, some promising antibiofilm approaches, such as theranostics, biofilm structure destruction, and quorum sensing inhibition, are also demonstrated. Finally, we conclude the current antibiofilm nanotechnologies and discuss the challenges and future directions in this field. Abstract : Bacterial biofilm related infections are ever growing threats for global medical community. However, traditional antibiotic therapy is usually ineffective for eradicating bacterial biofilms. In this review, recent development of nanomedicine to treat bacterial biofilm infections is introduced, and typical therapeutic strategies based on nanotechnology are summarized and discussed herein.